Etnobotani Penghasil Getah oleh Suku Anak Dalam di Taman Nasional Bukit Duabelas Kabupaten Sarolangun, Jambi - Rana Rio Andhika; Bambang Hariyadi; Fachruddin Saudagar (Jurnal Ilmu Pertanian Indonesia, 2015)
Sap of plants is one of the non-timber forest products are used by the community Suku Anak Dalam (SAD) in the National Park Bukit Duabelas. SAD is Jambi tribal culture that has potential in utilized and protected forest biodiversity Bukit Duabelas National Park. This research aims at produced an inventory of plant sap, assess the utilization and preservation process and review process by SAD inheritance knowledge about produced plants to the next generation in National Park Bukit Duabelas Sarolangun, Jambi. Data collected by snowball sampling technique through in-depth interviews, participant observation, and documentation. Analysis of descriptive data. Based on the results of this study found 21 species of plants produced sap utilized by the SAD as a source of revenue, material treatment, fuel, hunting, adhesives, traditional rituals materials, dyes and other materials exudate freezer. SAD sources of knowledge on the use of plant sap derived from the shaman, the parents and their own experiences orally handed down to posterity.